(untitled) - Collis, Jill (New York, 2003)
Business Researchprovides a clear and practical guide for undergraduate research methods courses and individual research projects at both undergraduate and postgraduate level. The second edition retains the strong conceptual underpinning and practical orientation that has proved so popular with lecturers and students and introduces a number of new features.
Keywords: Business,Business; Research,Methodology